Studi Literatur: Peran Guru dalam Mengintegrasikan Literasi Membaca pada Pembelajaran Tematik di Sekolah Dasar - Nurfaira Syahda, Alya; Mustika, Dea; Nuroniyah, Balqis; Gina Salsabillah, Hafifah; Kurnia, Indah; Nofita Putri, Veriska (Jurnal Tinta, 2025)
The low level of reading literacy among elementary school students in Indonesia remains a fundamental challenge in education, particularly with the implementation of the thematic curriculum that requires the integration of various basic competencies. This study aims to identify the strategic role of teachers, effective implementation strategies, and the challenges encountered in integrating literacy into thematic learning. A qualitative literature review method was employed by analyzing ten relevant national journal articles. The findings indicate that teachers play a pivotal role as facilitators, innovators, and designers of learning experiences. Effective integration strategies include the use of the webbed-type integrated learning model, utilization of creative media, and the implementation of literacy-based projects. However, several challenges were identified, such as limited instructional time, lack of methodological variation, and difficulties in aligning literacy content with thematic materials. It is concluded that the success of literacy integration in thematic learning heavily depends on the active and creative role of teachers, which must be supported by a collaborative and sustainable educational ecosystem.